2015
DOI: 10.1021/acs.joc.5b01802
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Mechanism of the Pechmann Condensation Reaction Using NMR

Abstract: The mechanism of the Pechmann condensation is still controversial despite the technological and biochemical importance of coumarins. Here, we present NMR evidence for a mechanism featuring the sequence of initial electrophilic aromatic substitution followed by transesterification and a final dehydration. This mechanism has been convincingly defined and supported by the temporal evolution of two key intermediates which could be purified and identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 15 publications
(32 reference statements)
0
7
0
2
Order By: Relevance
“…The cinnamic ester derivative was also reported as a side product of the Pechmann condensation. 20 Tyndall and coauthors 36 monitored the reaction between resorcinol (1b) and ethyl 4,4,4trifluoroacetoacetate (2c) using 19 F NMR and 1 H NMR. In this study, iodine was used as catalyst and toluene as solvent.…”
Section: Resultsmentioning
confidence: 99%
“…The cinnamic ester derivative was also reported as a side product of the Pechmann condensation. 20 Tyndall and coauthors 36 monitored the reaction between resorcinol (1b) and ethyl 4,4,4trifluoroacetoacetate (2c) using 19 F NMR and 1 H NMR. In this study, iodine was used as catalyst and toluene as solvent.…”
Section: Resultsmentioning
confidence: 99%
“…The intermediate rapidly cyclizes through an intramolecular condensation (a S E Ar type reaction) followed by dehydration. However, there are NMR studies that have concluded that the sequence of events is different, i.e., the condensation begins with the activation of the β-keto group (protonation or complexation with a Lewis acid, path B) followed by electrophilic aromatic substitution, cyclization, and final dehydration [69]. It was found that the reaction can be promoted not only by homogenous catalysts, but also by convenient reusable or magnetically recoverable particles [70][71][72] or ionic liquids [73] carrying protic or Lewis acids.…”
Section: Coumarins: Synthesis Structures and Propertiesmentioning
confidence: 99%
“…The immense interest in the biological and medicinal importance of coumarin derivatives has triggered the development of various catalysts and reactions conditions in this regard. In addition, the mechanism undelaying the Pechmann condensation, which is still controversial, has been discussed in depth by both theoretical and experimental methods [ 9 , 10 , 11 ]. Recently, advances in the synthesis of coumarins via the Pechmann condensation have been extensively reviewed [ 12 ].…”
Section: Synthetic Routes Toward Central 2-pyrone Of 4-arylcoumarimentioning
confidence: 99%